2020
DOI: 10.1007/s00414-019-02208-9
|View full text |Cite
|
Sign up to set email alerts
|

Mongolian spots as a finding in forensic examinations of possible child abuse–implications for case work

Abstract: Mongolian spots (MS) are congenital dermal conditions resulting from neural crest-derived melanocytes migration to the skin during embryogenesis. MS incidences are highly variable in different populations. Morphologically, MS present as hyperpigmented maculae of varying size and form, ranging from round spots of 1 cm in diameter to extensive discolorations covering predominantly the lower back and buttocks. Due to their coloring, which is also dependent on the skin type, MS may mimic hematoma thus posing a cha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 39 publications
0
6
0
Order By: Relevance
“…The 1.5-year-old girl presented Mongolian spots on the back and on the right side of the trunk, which according to the classification of Kettner et al [14] can be categorized as type III. Kolbe et al [15] reported a 2-month-old girl with extensive Mongolian spots on the back of the trunk, buttocks and both ankles.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The 1.5-year-old girl presented Mongolian spots on the back and on the right side of the trunk, which according to the classification of Kettner et al [14] can be categorized as type III. Kolbe et al [15] reported a 2-month-old girl with extensive Mongolian spots on the back of the trunk, buttocks and both ankles.…”
Section: Discussionmentioning
confidence: 99%
“…Kettner et al were able to detect Mongolian spots at different locations in 10.27% of 253 children examined. The authors developed a classification scheme according to localization (I -buttocks, II -not buttocks, IIIcombination of I and II) with several subtypes [14].…”
Section: Discussionmentioning
confidence: 99%
“…Other features by which melanosis spots can be differentiated from abusive hematomas are, for example, their blurred borders and the absence of associated tenderness, erythema, or swelling [ 30 , 31 ]. Even though there is a low incidence of these spots in the Caucasian (European) population, it is important to know this phenotype in order to distinguish it from child maltreatment [ 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…The skin is the largest and most exposed organ [ 23 ]. Cutaneous conditions such as congenital dermal melanocytosis (Mongolian spots), capillary hemangiomas, and arteriovenous malformations can masquerade as skin findings of suspected abuse [ 28 , 29 ]. Heritable hematological disorders such as Bernard-Soulier syndrome (BSS), Glanzmann thrombasthenia (GT), Von Willibrand disease (VWD), hemophilia disorders, and Wiskott-Aldrich syndrome have also been misconstrued for physical abuse [ 22 ].…”
Section: Discussionmentioning
confidence: 99%